COMPARATIVE EVALUATION OF OUTCOMES OF DRAINAGE TECHNIQUES IN VITRECTOMY FOR RHEGMATOGENOUS RETINAL DETACHMENT. Issue 1 (January 2022) - Kumari, Neha; Surve, Abhidnya; Kumar, Vinod; Azad, Shorya V.; Chawla, Rohan; Venkatesh, Pradeep; Vohra, Rajpal; Kumar, Atul
Abstract : Purpose: To compare the anatomical and functional outcomes of drainage through posterior retinotomy versus perfluorocarbon liquid (PFCL)–assisted drainage in vitreoretinal surgery for rhegmatogenous retinal detachment and to study intraoperative and postoperative complications. Methods: This was a prospective randomized study of 52 cases who underwent vitreoretinal surgery for rhegmatogenous retinal detachment. Group 1 underwent PFCL-assisted drainage through preexisting break, whereas Group 2 had posterior retinotomy to drain subretinal fluid. Cases were evaluated for retinal reattachment rates, visual outcomes, optical coherence tomography parameters, and postoperative metamorphopsia. The patients were followed up for minimum period of 3 months. Results: Two groups were comparable in terms of demographic and preoperative parameters. Both groups had single surgery success rate of 100% by the end of follow-up. Final best-corrected visual acuity in Group 1 was 0.61 ± 0.33 and 0.61 ± 0.32 in Group 2 ( P = 0.77). Optical coherence tomography parameters (foveal contour, retinal layers, central macular thickness, and epiretinal membrane formation) were similar between the two groups. Subjective metamorphopsia was present in 30.77% (8 of 26) patients in Group-1 and 69.23% (18 of 26) patients in Group-2 ( P = 0.034). One eye had retained subretinal PFCL away from the macula in Group 1. Conclusion: Anatomical and functional outcomes were similar in vitrectomy using PFCL-assisted drainage versus posterior retinotomy drainage. Postoperative metamorphopsia was lesser in patients who underwent PFCL-assisted drainage through the pre-existing break. Abstract : The anatomical and functional outcomes in vitrectomy for fresh rhegmatogenous retinal detachment were similar in patients undergoing posterior retinotomy and perfluorocarbon liquid–assisted drainage of subretinal fluid. However, postoperative metamorphopsia was less common in patients undergoing perfluorocarbon liquid–assisted drainage.